A potential Cu/V-organophosphonate platform for tailored void spaces via terpyridine mold casting - Bulut, Aysun; Worle, Michael; Zorlu, Yunus; Kirpi, Erdogan; Kurt, Huseyin; Zubieta, Jon; Grabowsky, Simon; Beckmann, Jens; Yucesan, Gundog (INT UNION CRYSTALLOGRAPHY, 2017)
The reaction of appropriate copper and vanadium salts with tetratopic methane tetra-p-phenylphosphonic acid (MTPPA) in the presence of 2,2':6':2 ''-terpyridine (terpy) yielded the three-dimensional bimetallic copper vanadium phosphonate framework [{Cu(terpy)}(4)Cu(VO2)(4)(MTPPA-H)(2)]center dot 4H(2)O (1). Terpy has no net contribution to the three-dimensional structure providing a potential platform for void space formation via mold-casting. The structure was characterized by single-crystal X-ray diffraction and thermogravimetric analysis (TGA). Magnetic measurements were performed using a SQUID magnetometer. The crystal structure of the methanol solvate of the free ligand, MTPPA center dot MeOH, was analysed using Hirshfeld surfaces and fingerprint plots.
Keywords: metal organic frameworks (MOFs); organophosphonate complexes; bimetallic Cu-V frameworks; Hirshfeld surfaces; void space formation; METAL-ORGANIC FRAMEWORKS; STATE COORDINATION CHEMISTRY; SOLID-STATE; CRYSTAL-STRUCTURES; STRUCTURAL-CHARACTERIZATION; SUPRAMOLECULAR CHEMISTRY; HYDROTHERMAL SYNTHESIS; PHOSPHONATES SYNTHESIS; BUILDING-BLOCK; V/P/O LAYERS; Chemistry; Crystallography